Assessment for student motivation a professional development DVD - Stiggins, Richard J.; Assessment Training Institute (Portland, Or. : Assessment Training Institute, 2004)
Video helps educators understand why and how behavior management (manipulation of rewards and punishments) defined the relationship between assessment and student motivation in schools for decades
Title from disc
User's guide on CD-ROM
Presenter: Rick Stiggins
Keywords: Classroom management; Motivation in education; Behavioral assessment; Behavior modification